Maternal exercise increases but concurrent maternal fluoxetine prevents the increase in hippocampal neurogenesis of adult offspring. (May 2018) - Gobinath, Aarthi R.; Wong, Sarah; Chow, Carmen; Lieblich, Stephanie E.; Barr, Alasdair M.; Galea, Liisa A.M.
Highlights: Maternal exercise increased dorsal hippocampal neurogenesis in adult offspring. Maternal postpartum fluoxetine reduced dorsal hippocampal neurogenesis in offspring. Maternal postpartum fluoxetine and exercise reduced HPA axis activity in males. Maternal exercise impaired HPA axis activity in female offspring. Abstract: Treating postpartum depression (PPD) with pharmacological antidepressants like fluoxetine (FLX) is complicated because these drugs can remain active in breast milk and potentially affect infant development. Alternatively, non-pharmacological treatments such as exercise are associated with beneficial effects on infant development but its potential ability to counter the effects of PPD are largely unknown. To investigate this, we treated dams with corticosterone (CORT) or vehicle (sesame oil) from postpartum days 2–25 to model PPD. Within oil and CORT treatments, dams were also assigned to one of these treatments: 1) exercise (voluntary running wheel) + FLX (10 mg/kg, i.p.), 2) exercise + saline (vehicle for FLX), 3) no exercise + FLX, 4) no exercise + saline. Both male and female offspring were analyzed, and this generated a total of 16 experimental groups for this study. Adult male and female offspring (125 d old) of these dams were tested for anxiety-like behavior in the novelty suppressed feeding test and stress reactivity in the dexamethasone suppression test. Hippocampal tissue was processed for doublecortin, a protein expressed in immature neurons. Regardless of sex, maternal exercise increased neurogenesis in the dorsal hippocampus of adult offspring, but concurrent exposure to maternal fluoxetine prevented this effect. Exposure to either maternal exercise or maternal FLX facilitated HPA negative feedback in adult males but not females. Maternal postpartum CORT also facilitated HPA feedback in adult offspring of both sexes. Collectively, these data indicate that maternal exercise increased dorsal hippocampal neurogenesis in both sexes but differentially affected offspring HPA axis based on sex. Alternatively, maternal postpartum FLX facilitated HPA axis negative feedback only in males. These findings indicate that different types of maternal interventions bear long-term effects on offspring outcome with implications for treating PPD.